2008
DOI: 10.1542/peds.2007-3650
|View full text |Cite
|
Sign up to set email alerts
|

Experience of Families During Cardiopulmonary Resuscitation in a Pediatric Intensive Care Unit

Abstract: This study supports encouraging family presence during cardiopulmonary resuscitation. The majority of parents who had been present and those who had not been present believed that all families should be given the option to be present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
133
0
10

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(149 citation statements)
references
References 21 publications
2
133
0
10
Order By: Relevance
“…However, presence during resuscitation in the emergency department has been shown to be psychologically beneficial for family members, particularly if the attempt is unsuccessful, as it decreases post-traumatic stress 23 and facilitates the grieving process 24 . There is very little literature exploring this concept in the prehospital setting, although it has been suggested that parental accompaniment in paediatric trauma requiring helicopter retrieval is probably beneficial for both the patient and the family 25 .…”
Section: Parents and Carersmentioning
confidence: 99%
“…However, presence during resuscitation in the emergency department has been shown to be psychologically beneficial for family members, particularly if the attempt is unsuccessful, as it decreases post-traumatic stress 23 and facilitates the grieving process 24 . There is very little literature exploring this concept in the prehospital setting, although it has been suggested that parental accompaniment in paediatric trauma requiring helicopter retrieval is probably beneficial for both the patient and the family 25 .…”
Section: Parents and Carersmentioning
confidence: 99%
“…In einigen westlich orientierten Gesellschaften wünscht die Mehrzahl der Eltern, bei der Reanimation ihres Kindes anwesend zu sein [401,402,403,404,405,406,407,408,409,410]. Dabei wird die Anwesenheit der Eltern wird vom medizinischen Personal üblicherweise nicht als störend [403,411,412,413,414,415] oder Stress erhöhend wahrgenommen [401,403,412].…”
Section: Anwesenheit Der Elternunclassified
“…Dabei wird die Anwesenheit der Eltern wird vom medizinischen Personal üblicherweise nicht als störend [403,411,412,413,414,415] oder Stress erhöhend wahrgenommen [401,403,412]. Eltern, die bei der Reanimation ihres Kindes anwesend sein wollen, glauben, dass sich ihr Beisein positiv auf ihr Kind auswirkt [401,402,403,410,414,415,416,417]. Wird den Eltern erlaubt, an der Seite ihres Kindes zu bleiben, kön-nen sie leichter eine realistische Einschät-zung der therapeutischen Bemühungen und des Todes ihres Kindes erlangen.…”
Section: Anwesenheit Der Elternunclassified
See 1 more Smart Citation
“…[2][3][4][5][6][7][8][9][10][11][12][13] Despite recommendations from professional organizations, consensus conferences, joint position and policy statements, and clinical practice guidelines regarding family presence during resuscitation, [14][15][16][17][18][19][20][21][22][23][24][25][26] only 5% of critical care units in the United States, 27 8% in Canada, 28 and 7% in Europe 29 have written policies that allow family presence. Surveys of nurses' practice indicate that many, if not most, critical care nurses have been asked by patients' family members if they could be present during resuscitation and invasive procedures and have brought such families to the bedside, despite the lack of formal written hospital policies.…”
mentioning
confidence: 99%